DEVELOPMENT OF ENVIRONMENTALLY FRIENDLY VEGETABLE INSECTICIDES BASED ON GADUNG BARK NANOEMULSION (DIOSCOREA HISPIDA DENNST) FOR COMMUNITY EMPOWERMENT IN RITING VILLAGE, ACEH BESAR - Lina, Eka Candra; Yasar, Muhammad; Zulham, Zulham; Mustaqimah, Mustaqimah; Agustina, Raida; Khairi, Khairi (LPPM Universitas Andalas, 2025)
The peel of gadung tuber (Dioscorea hispida Dennst), abundantly found in Riting Village, Aceh Besar, represents a local natural resource with potential use as an environmentally friendly botanical insecticide. Until now, gadung peel has been treated merely as waste from tuber processing and has no economic value, even though it contains bioactive compounds such as diosgenin and saponin, which are known to be toxic to insects. This community service program aimed to produce a nanoemulsion-based botanical insecticide sample derived from gadung peel extract, evaluate its effectiveness against Crocidolomia pavonana larvae, and enhance local community knowledge and skills in utilizing gadung peel waste as a raw material for botanical insecticide production. The program was carried out in two stages: (1) sample preparation and bioassay testing, and (2) knowledge transfer and hands-on training through workshops. The results showed that gadung peel extract significantly affected larval mortality, with LC₅₀ and LC₉₅ values of 0.682% and 1.469%, respectively. The workshops successfully improved participants’ understanding of gadung’s potential as a natural insecticide source, technical skills in handling raw materials, and the ability to formulate and apply simple botanical insecticides using local ingredients. Outputs of the activity included a training module, a technical guideline, and prototype products for further development. Overall, this program positively contributed to enhancing community capacity in sustainable agricultural innovation and promoting the utilization of local natural resources with economic and environmental benefits.